PERMAINAN “ABC 5 DASAR” UNTUK MENINGKATKAN PENGUASAAN KOSA KATA BAHASA ARAB - Khoirul Faizin (Muróbbî: Jurnal Ilmu Pendidikan, 2020)
Abstract: Media is one of the most important elements in learning. Because the influence of instructional media greatly affects the ability of students to capture material provided by the teacher. Good media is media that is in accordance with the conditions of students and not all media that use advanced technology rather than simple ones because the guidelines for making media are looking at the conditions of the environment and students. One of the most popular learning media for students is the game. The game invites students to learn by having fun, therefore, students will not feel objected and bored with the lesson because what they feel is playing and they unconsciously accept lessons from the game. One very communicative game is "ABC 5 Dasar". In this game students are invited to think and remember words in Arabic by making it part of the game. This study uses a development method and then the results of this research in the form of descriptive analysis that illustrates Arabic learning to improve Arabic vocabulary mastery or (mofradat) wrapped in traditional games in the form of the game "ABC 5 Dasar". It is hoped that this research can contribute to Arabic learning teachers to improve Arabic vocabulary mastery (mufradat).